2018
DOI: 10.1108/hff-06-2017-0220
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of transient flow field in a mixed-flow pump during starting period

Abstract: Purpose This paper aims to study the transient flow characteristics in a mixed-flow pump during the start-up period. Design/methodology/approach In this study, numerical calculation of the internal flow field in a mixed-flow pump using the sliding mesh method was carried out. The regulation of the pressure, streamline and the relative speed during the start-up period was analyzed. Findings The trend of the simulated head is consistent with the experimental results, and the calculated head is around 0.3 m h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…Literatures and our former researches concluded that, in spite its time-averaging simplification, the standard k-ɛ can provide a good result for the flow field in different types of pumps. 1,2,27 As a result, the standard k-ɛ model based on the Reynolds averaged Navier–Stokes equation is selected, as it offers a good compromise between computational effort and numerical accuracy. Steady simulations for different flow rates 0.2 Q des , 0.4 Q des , 0.6 Q des , 0.8 Q des , and 1.0 Q des are calculated for 1500 iterations at first, which is followed by the transient simulation using the steady field as the initial condition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Literatures and our former researches concluded that, in spite its time-averaging simplification, the standard k-ɛ can provide a good result for the flow field in different types of pumps. 1,2,27 As a result, the standard k-ɛ model based on the Reynolds averaged Navier–Stokes equation is selected, as it offers a good compromise between computational effort and numerical accuracy. Steady simulations for different flow rates 0.2 Q des , 0.4 Q des , 0.6 Q des , 0.8 Q des , and 1.0 Q des are calculated for 1500 iterations at first, which is followed by the transient simulation using the steady field as the initial condition.…”
Section: Methodsmentioning
confidence: 99%
“…The mixed-flow pump is widely used in agricultural irri- gation, thermal power plant, and chemical process systems, as it collects advantages of both centrifugal and axial flow pumps. 1,2 The head-flow characteristic of mixed-flow pumps is often required to keep in a small incline, which usually gives rise to unstable flow in the pump especially under part-loading discharge. 3 Recent researches in turbomachines reveal that the so called positive-slope characteristic on the head-flow curve is mainly caused by rotating stalls in the impellers or guide vanes.…”
Section: Introductionmentioning
confidence: 99%
“…Mixed-flow pump is a kind of industrial and agricultural pump, which could be widely used in irrigation, mine engineering, power stations and water supply [1][2][3][4]. It can meet the requirements of low head and high flow when operating at different situations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…e transient behavior of the pump was analyzed using pump characteristic curves [16]. Li et al [17] found that in the startup process of the mixed-flow pump, the flow stabilized in the impeller, the scale of vortex decreased gradually as the rotating speed approached the rated speed, and the transient effect disappeared.…”
Section: Introductionmentioning
confidence: 99%